Proceedings of the 1997 IEEE/RSJ International Conference on Intelligent Robot and Systems. Innovative Robotics for Real-World
DOI: 10.1109/iros.1997.656803
|View full text |Cite
|
Sign up to set email alerts
|

Automatic parallel parking and returning to traffic manoeuvres

Abstract: This video illustrates a control approach developed to perform parallel parking and returning to traffic maneuvers for a car capable of autonomous motion. The key idea is t o carry out a motion control procedure involving a "Localization-Planning-Execution" cycle until a specified location of the car relative to its environment is reached. Range measurements are used to model environmental objects around the car. The automatic maneuvers developed are demonstrated o n an experimental electric autonomous car in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Research studies that considered general parking scenarios are scarce. Apart from Paromtchik & Laugier's three publications in the early years (i.e., [28][29][30]), no other reverent studies can be found, to the best of our knowledge. As a brief summary, no study has solved or can solve the aforementioned three issues altogether.…”
Section: Introductionmentioning
confidence: 85%
“…Research studies that considered general parking scenarios are scarce. Apart from Paromtchik & Laugier's three publications in the early years (i.e., [28][29][30]), no other reverent studies can be found, to the best of our knowledge. As a brief summary, no study has solved or can solve the aforementioned three issues altogether.…”
Section: Introductionmentioning
confidence: 85%
“…The necessary conditions are given in essay [11], and a complex algorithm for solving flat outputs is given in essay [12]. in practical applications, a set of outputs is often selected according to physical meaning, and then it is verified whether the set of outputs conforms to formula (5).…”
Section: Definition Of Differential Flatnessmentioning
confidence: 99%
“…Literature [4] proposed an easy way to plan the parking trail based on two tangent circular arcs. Literature [5] compute the parking path through fitting sinusoidal curve based on regression algorithm. Multi-constrained optimization method is used in [6] to plan the ideal parking path through fitting arctangent curve.…”
Section: Introductionmentioning
confidence: 99%
“…Our local planner builds on the existing work in discrete search in unknown environments (e.g., [13], [8], [21]), as well as kinematic forward search [12], [16], [26] and nonlinear optimization in the space of 2D curves [4]. Whereas strategies for specific dedicated parking maneuvers have been developed [22], [23] and nowadays are even available in off-the-shelf vehicles, these systems perform autonomous navigation only in a short range and are not able to plan complex navigation tasks through entire parking structures. The work probably most closely related to ours is that of Schanz et al [27] who developed an autonomous parking system in a subterranean parking structure.…”
Section: Introductionmentioning
confidence: 99%